Global guidelines trends and controversies in lower limb venous and lymphatic disease: Narrative literature revision and experts' opinions following the vWINter international meeting in Phlebology, Lymphology & Aesthetics, 23–25 January 2019. (September 2019) - Gianesini, Sergio; Obi, Andrea; Onida, Sarah; Baccellieri, Domenico; Bissacco, Daniele; Borsuk, Denis; Campisi, Corradino; Campisi, Cesare Corrado; Cavezzi, Attilio; Chi, Yung-wei; Chunga, Juan; Corda, Domenico; et al.
Guidelines are fundamental in addressing everyday clinical indications and in reporting the current evidence-based data of related scientific investigations. At the same time, a spatial and temporal issue can limit their value. Indeed, variability in the recommendations can be found both among the same nation different scientific societies and among different nations/continents. On the other side, Garcia already published in 2014 data showing how, after three years in average, one out of five recommendations gets outdated (Martinez Garcia LM, Sanabria AJ, Garcia Alvarez E, et al. The validity of recommendations from clinical guidelines: a survival analysis. CMAJ 2014;186(16):1211–1219). The present document reports a narrative literature revision on the major international recommendations in lower limb venous and lymphatic disease management, focusing on the different countries' guidelines, trends and controversies from all the continents, while identifying new evidence-based data potentially influencing future guidelines. World renowned experts' opinions are also provided. The document has been written following the recorded round tables scientific discussions held at the vWINter international meeting (22–26 January 2019; Cortina d'Ampezzo, Italy) and the pre- and post-meeting literature search performed by the leading experts.